Manufacturing Tolerance Analysis of Deep-Ridged 90° Hybrid Based on InP 4 × 4 MMI - Ziqing Lu; Qin Han; Han Ye; Shuai Wang; Feng Xiao (Photonics, 2020)
An optical 90° hybrid based on an InGaAsP/InP deep-ridged 4 × 4 multimode interference (MMI) coupler is proposed and fabricated. Manufacturing tolerances on structural parameters of the 90° hybrid including multimode waveguide width and length, waveguide core thickness, and refractive index are analyzed over the whole C-band using a three-dimensional beam propagation method (3D BPM). The simulation results show that the 90° hybrid is insensitive to the interference length with a deviation of 10 μm. However, the width fluctuations produce far stronger performance variations than length fluctuations. The common-mode rejection ratios (CMRRs) are always above 40 dB, and the phase error (PE) is always below 2.5° with the fluctuations of the refractive index by 0.01 and the thickness by 0.1 μm of the core layer. The fabricated device exhibited a quadrature phase response with a high common-mode rejection ratio of more than 25 dB and a small phase error of less than 5° from 1545 nm to 1560 nm.